Production of Inter-Genus Somatic Nuclear Transferred Gonadal Germ Cells (snt-GGCs) in Avian Species - Susumu Ishiguro; Yukio Kanai; Atsushi Tajima (The Journal of Poultry Science, 2008)
Interspecies or even inter-genus somatic nuclear transfer is considered to be an effective means for conserving a wide variety of avian genetic resources. However, somatic nuclear transfer offspring production is currently limited to mammals. Therefore, the present experiment was designed in an attempt to produce inter-genus somatic nuclear transferred gonadal germ cells (snt-GGCs) between chicken and quail. Electrofusion was carried out between embryonic blood cells (EBCs) collected from 4-day-old embryos (donor cells) and gonadal germ cells (GGCs) from 7-day-old chick embryos or 6-day-old quail embryos (recipient cells). GGCs were labeled with PKH26 fluorescent dye as a marker. Electrofusion was carried out according to previously described methods. The combinations of donor-recipient cells were designed to contain all four possible combinations: E(c)-G(c), E(q)-G(q), E(q)-G(c) and E(c)-G(q), where E, G, c and q are abbreviations for EBCs, GGCs, chick and quail, respectively. Following electrofusion, the fusion solution containing cells were stained with 1μg/mL Hoechst 33342. PKH26-labeled cells with two or more nuclei of different sizes were determined to be snt-GGCs. The experiment was replicated ten times and snt-GGCs were observed in five (50%), three (30%), four (40%) and five (50%) replicates. The average number of snt-GGCs produced per replicate were 0.6 (1.2%), 0.3 (0.6%), 0.5 (1.0%) and 0.5 (1.0%) for E(c)-G(c), E(q)-G(q), E(q)-G(c) and E(c)-G(q), respectively. The present results demonstrate that inter-genus snt-GGCs can be produced by electrofusion using EBCs and GGCs in avian species.